Stable conversion of metastable hydrates in calcium aluminate cement by early carbonation curing. (October 2017) - Park, S.M.; Jang, J.G.; Son, H.M.; Lee, H.K.
Highlights: Effect of early carbonation curing on calcium aluminate cement was investigated. Carbonation of metastable hydrates induced no significant change in porosity. Carbonation curing allowed stable conversion of metastable hydrates. Abstract: The hydration of monocalcium aluminate in calcium aluminate cement forms metastable products such as CAH10 and C2 AH8, which undergo phase transformations into stable products, inducing significant volumetric instability. The present study adopted carbonation curing, in which a calcium aluminate cement paste is exposed to a CO2 concentration of 10%. X-ray diffractometry, thermogravimetry and mercury intrusion porosimetry were conducted on the carbonation-cured and on reference samples at 28 days. The results showed that the metastable phases in the carbonation-cured sample were converted into stable phases and calcium carbonate polymorphs without inducing any significant change in the pore structure. This study may provide new insight into innovative means of avoiding the unstable conversion of hydrates in calcium aluminate cement by utilizing CO2 collected from industrial sources.